2010
DOI: 10.1007/s10517-010-0862-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Central Neurotransmitters on Heart Rate Variability in Outbred Rats at Rest and during Acute Stress: Nature of Very-Low-Wave Spectrum Component Revisited

Abstract: We studied the effect of blockade of neurotransmitter monoamine reuptake and inhibition of catecholamine synthesis on heart rate variability in outbred albino rats at rest and during acute stress. Amitriptyline increased, while α-methyltyrosine reduced the power of VLF waves in heart rate variability spectrum. The effect of amitriptyline manifested at rest and was most striking under stressful conditions, while the effect of α-methyltyrosine was observed only under conditions of acute stress. This suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…By the age of 21 days, the HR reached the maximum values, which was in line with a previous report [9]. This was paralleled by the fi rst increase of spectral power (2.6 times; p<0.001) due to more intense slow waves: 5.8 times for LF (p<0.001) and 19.8 times for VLF (p<0.001), which could indicate stimulation of the cerebral CAergic systems [6] and of suprasegmentary regulation level [1]. Due to more complex wave structure, the cardiac rhythm became less strained (in comparison with that in 14-day-old rats), SI decreased by 1.8 times (p<0.01), but remained signifi cantly higher than 100 arb.…”
Section: Resultssupporting
confidence: 91%
“…By the age of 21 days, the HR reached the maximum values, which was in line with a previous report [9]. This was paralleled by the fi rst increase of spectral power (2.6 times; p<0.001) due to more intense slow waves: 5.8 times for LF (p<0.001) and 19.8 times for VLF (p<0.001), which could indicate stimulation of the cerebral CAergic systems [6] and of suprasegmentary regulation level [1]. Due to more complex wave structure, the cardiac rhythm became less strained (in comparison with that in 14-day-old rats), SI decreased by 1.8 times (p<0.01), but remained signifi cantly higher than 100 arb.…”
Section: Resultssupporting
confidence: 91%
“…These findings present new research opportunities, as the power at VLF is related to changes in the humoral system 27 , while DFA fluctuations have been considered useful when analyzing the intrinsic behavior of a system 28 . Finally, the age of the participants influenced the final prediction model of VO 2max , with correlations of r = 0.423 in men and r = 0.212 in women, which has been considered in the development of other prediction models 29 .…”
mentioning
confidence: 99%
“…The increased LF power following stress was reported by many previous studies utilizing various stress models including psychological stress [ 59 ], social defeat stress [ 13 , 52 ] and the CMS model [ 16 , 17 ]. On the contrary, most studies showed that the HF power was either unchanged [ 60 ] or decreased [ 16 , 17 , 52 ]. Therefore, the increase in HF power at 4 weeks in this study was unexpected.…”
Section: Discussionmentioning
confidence: 99%